Laser Microdissection of the Alveolar Duct Enables Single-Cell Genomic Analysis - Bennett, Robert D.; Ysasi, Alexandra B.; Belle, Janeil M.; Wagner, Willi L.; Konerding, Moritz A.; Blainey, Paul C.; Pyne, Saumyadipta; Mentzer, Steven J. (Frontiers in Oncology, 2014)
Complex tissues such as the lung are composed of structural hierarchies such as alveoli, alveolar ducts and lobules. Some structural units, such as the alveolar duct, appear to selectively participate in tissue regeneration. Here, we demonstrate an approach to conduct laser microdissection of the lung alveolar duct for single-cell PCR analysis. Our approach involved three steps. 1) The initial preparation used mechanical sectioning of the lung tissue with sufficient thickness to encompass the structure of interest. In the case of the alveolar duct, the precision-cut lung slices were 200um thick; the slices were processed using near-physiologic conditions to preserve the state of viable cells. 2) The lung slices were examined by transmission light microscopy to target the alveolar duct. The air-filled lung was sufficiently accessible by light microscopy that counterstains or fluorescent labels were unnecessary to identify the alveolar duct. 3) The enzymatic and microfluidic isolation of single cells allowed for the harvest of as few as several thousand cells for PCR analysis. Microfluidics based arrays were used to measure the expression of selected marker genes in individual cells to characterize different cell populations. Preliminary work suggests the unique value of this approach to understanding the intra- and intercellular interactions within the regenerating alveolar duct.